Little women - DiNovi, Denise; Swicord, Robin; Armstrong, Gillian 1950-; Ryder, Winona 1971-; Sarandon, Susan 1946-; Byrne, Gabriel 1950-; Alvarado, Trini; Mathis, Samantha; Dunst, Kirsten; Danes, Claire 1979- (Columbia Pictures, 1994)
A classic coming-of-age story set during the Civil War, "Little Women" follows the childhood adventures of the four free-spirited March sisters. With their father away fighting in the Civil War, Joe, Meg, Beth and Amy grow up with their mother in somewhat reduced circumstances. They are a close family who inevitably have their squabbles and tragedies. But the bond holds even when, later, men friends start to become a part of the household.